RESEARCH INTO THE AERODYNAMICS OF AIR FLOWS IN CYCLONES - Petrov, V.; Аlеksashyn, А.; Poznar, S. (Zernovì produkti ta kombìkorma, 2025)
Human health is of high value, therefore, with the development of industry, the requirements for the impact on ecology and occupational safety and health ohs, including air quality, are increasing. There are many ways to purify air, one of which is cyclone separators (hereinafter: cyclones): horizontal and vertical. The geometric dimensions of cyclones depend on the volume of purified air, and the efficiency of purification depends on the design, therefore, cyclone designs must have optimal geometric parameters for effective dust removal. Models of vertical cyclones, worked out over the years, are widely used in the grain processing industry. Horizontal cyclones are less studied and have lower efficiency, but they are used in aggregate equipment, where they have certain advantages. In order to get further improvement, the models of horizontal cyclones, comparative studies of two types of cyclones were performed. The methodology for studying the aerodynamics of swirling air flow in difficult cyclone conditions in the ANSYS CFX package was applied. Three-dimensional models of horizontal and vertical cyclones designed for the same volume of purified air were made. In accordance with the recommendations the models of theoretical calculations and air flow parameters were taken into account. A 3d-mesh was built on the models of the study objects using the finite element method. Initial data and boundary conditions were assigned. The design of a horizontal cyclone used with the A1-BLC separator was taken as the object of study. The pressure isobars in various auxiliary vertical and horizontal planes are calculated. The lines of equal air flow velocities and their vector analogues were built, zones of maximum and minimum pressure on the cyclone elements were determined. The correspondence of the general pattern of pressure distribution along the wall in the circumferential direction was determined. The loads on the cyclone structural elements were calculated when the aerodynamic coefficient changes. The calculations were performed using a functional calculator with ANSYS CFX package. The air flow pressure on the inner cone was calculated by the finite element method using the ANSYS CFX package at an air velocity of 12 m/s. To verify the numerical correlation of the results obtained when studying the horizontal cyclone, a standard model of a vertical cyclone was used. Due to the movement (animation) of the auxiliary vertical planes, it is possible to consider the dynamics of changes in pressure and velocities of the dusty air flow in the calculated volume.